2016
DOI: 10.1111/ane.12667
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the use of magnetic resonance imaging in diagnosing and monitoring the treatment of multiple sclerosis: recommendations of the Swedish Multiple Sclerosis Association and the Swedish Neuroradiological Society

Abstract: Multiple sclerosis (MS) is associated with inflammatory lesions in the brain and spinal cord. The detection of such inflammatory lesions using magnetic resonance imaging (MRI) is important in the consideration of the diagnosis and differential diagnoses of MS, as well as in the monitoring of disease activity and predicting treatment efficacy. Although there is strong evidence supporting the use of MRI for both the diagnosis and monitoring of disease activity, there is a lack of evidence regarding which MRI pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 44 publications
(103 reference statements)
2
55
0
1
Order By: Relevance
“…Furthermore, previous research has shown that the robustness of FreeSurfer, along with other segmentation tools, varies across scanners and magnetic field strengths . We similarly found that the intrascanner repeatability is higher than interscanner reproducibility, corroborating previous recommendations that one should use the same MRI scanner and imaging parameters during routine MS follow‐up …”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, previous research has shown that the robustness of FreeSurfer, along with other segmentation tools, varies across scanners and magnetic field strengths . We similarly found that the intrascanner repeatability is higher than interscanner reproducibility, corroborating previous recommendations that one should use the same MRI scanner and imaging parameters during routine MS follow‐up …”
Section: Discussionsupporting
confidence: 87%
“…A standard protocol for MS was used with 3D T1‐weighted sequence following a dose of intravenous gadolinium (Gd) contrast, T2‐weighted sequence, and 3D fluid‐attenuated inversion recovery sequence according to Swedish MS guidelines (Vagberg et al . ). The number of T2‐weighed and contrast‐enhancing T1 lesions were recorded (Table ).…”
Section: Methodsmentioning
confidence: 97%
“…International expert groups, such as the European MAGNIMS Group and the Canadian/North American Consortium of MS Centers (CMSC), have a introduced a standardized protocol for imaging of the brain (▶table 1) and the spinal cord (▶table 2) based on recent developments in the field of MS imaging [4][5][6]. These suggestions are increasingly implemented by national specialist groups [29]. There are special issues regarding MRI examination of the optic nerve that should include dedicated pulse sequences as in a standardized acquisition protocol as suggested by international expert panel guidelines [30].…”
Section: Standardized Examination Protocolmentioning
confidence: 99%